2014
DOI: 10.1002/cyto.a.22581
|View full text |Cite
|
Sign up to set email alerts
|

Quality assessment program forEuroFlow protocols: Summary results of four‐year (2010–2013) quality assurance rounds

Abstract: Flow cytometric immunophenotyping has become essential for accurate diagnosis, classification, and disease monitoring in hemato-oncology. The EuroFlow Consortium has established a fully standardized "all-in-one" pipeline consisting of standardized instrument settings, reagent panels, and sample preparation protocols and software for data analysis and disease classification. For its reproducible implementation, parallel development of a quality assurance (QA) program was required. Here, we report on the results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
125
1
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 135 publications
(138 citation statements)
references
References 22 publications
10
125
1
2
Order By: Relevance
“…Harmonization, or even standardization, of methods may narrow differences and improve validity of conclusions from multicenter studies, as has been demonstrated within the Euroflow consortium. 30 Hence, grouping of data per technical procedure could have been informative from a practical perspective; yet, the power of the analyses within and between numerous subgroups of centers would have been strongly limited by sample sizes. Notably, in daily practice, FC results in subjects suspected of MDS should preferably be compared with a center's own cohort of control samples.…”
mentioning
confidence: 99%
“…Harmonization, or even standardization, of methods may narrow differences and improve validity of conclusions from multicenter studies, as has been demonstrated within the Euroflow consortium. 30 Hence, grouping of data per technical procedure could have been informative from a practical perspective; yet, the power of the analyses within and between numerous subgroups of centers would have been strongly limited by sample sizes. Notably, in daily practice, FC results in subjects suspected of MDS should preferably be compared with a center's own cohort of control samples.…”
mentioning
confidence: 99%
“…Results that are neither standardized nor harmonized may lead to erroneous clinical, financial, regulatory, or technical decisions. The need for extensive expertise to analyze MFC data, together with lack of well-standardized and harmonized MFC-MRD methods [59], has been pointed out as the main drawback of MFC immunophenotyping [60]. In recent years, new multivariate computational tools and visualization plots have been developed and integrated into innovative software for multidimensional identification and classification of different cells coexisting in a sample.…”
Section: Multiple Myeloma Minimal Residual Disease (Mrd) and Flow Cymentioning
confidence: 99%
“…В связи с тем, что данные иммунофено-типирования (ИФТ) используются для стратификации пациентов в рамках крупных многоцентровых иссле-дований по терапии ОЛЛ, необходима максимально возможная стандартизация данного метода диагности-ки. В европейских и американских исследовательских группах эта проблема решается двумя путями: либо централизацией диагностики в нескольких крупных лабораториях, специалисты которых обладают доста-точным опытом работы, либо проведением жесткой процедуры стандартизации работы большого количества лабораторий, включающей контроль работы прибора, использование унифицированных панелей монокло-нальных антител, автоматический анализ данных при помощи специального программного обеспечения [4,5].…”
Section: цель данной работы -сравнение результатов интерпретации даннunclassified